Предмет: Алгебра,
автор: Ульяна6996
Упростите выражение (2-c)^2-c (c+4)
Ответы
Автор ответа:
0
(2-c)²-c(c+4)=
=2²-2.2.c+c²-c²-4c=4-4c-4c=4-8c
=2²-2.2.c+c²-c²-4c=4-4c-4c=4-8c
Автор ответа:
0
(2-c)^2-c (c+4)= 4-4с+с^2- с^2- 4с= 4
Ответ: 4
Автор ответа:
0
Ой, нет. Ошибся, там будет:4-8с, т.к. я не заметил(а) минус у 4.
Похожие вопросы
Предмет: Русский язык,
автор: naziraslekishina
Предмет: Қазақ тiлi,
автор: amirxankzormanov
Предмет: Математика,
автор: m6855030
Предмет: Математика,
автор: karina66639